2005
DOI: 10.1093/ajcn/82.1.140
|View full text |Cite
|
Sign up to set email alerts
|

A follow-up study of nutrient intake, nutritional status, and growth in infants with cow milk allergy fed either a soy formula or an extensively hydrolyzed whey formula

Abstract: Both nutritional status and growth were well within reference values in the 2 groups, and the selection of a formula can largely be made on the basis of infant tolerance to the formulas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 23 publications
1
20
1
Order By: Relevance
“…[6][7][8] Therefore, it is advisable to consume hypoallergenic formula, such as partially hydrolyzed milk or breast milk to avoid malnutrition. 2 In this study, we found no differences in nutritional status of infants with CMA between those who consumed breast milk and those who consumed hypoallergenic formula. The lack of difference is understandable, since both types of milk are excellent sources of nutrition for infants with CMA.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…[6][7][8] Therefore, it is advisable to consume hypoallergenic formula, such as partially hydrolyzed milk or breast milk to avoid malnutrition. 2 In this study, we found no differences in nutritional status of infants with CMA between those who consumed breast milk and those who consumed hypoallergenic formula. The lack of difference is understandable, since both types of milk are excellent sources of nutrition for infants with CMA.…”
Section: Discussioncontrasting
confidence: 57%
“…In addition, giving breast milk in the first 6 months of life is a cost-effective approach to provide the best nutrition for infants with CMA. [2][3][4] We aimed to compare the nutritional status of infants with CMA who consumed breast milk vs. hypoallergenic formula. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nutritional aspects of soy protein formulae have recently been reviewed by the ESPGHAN Committee on Nutrition [27]. Soy formulae support normal growth and nutrient status [28], but soy protein is inferior to CMP in its biological value for infants, with a lower digestibility and bioavailability of the protein and with lower methionine content [27]. Accordingly, European Union legislation on infant formulae requires a higher minimum protein content in soy formulae than CMP formulae (2.25 vs. 1.8 g/100 kcal).…”
Section: Breast Milk Substitutes For Infants With Cow's Milk Protein mentioning
confidence: 99%
“…Alternatively, soy protein and soy milk formulations for infant, adult, and agricultural use are safe to consume and have significant nutritional benefit (Messina, 1999;Slavin, 1991). In fact, soy formulations are so safe that they are routinely fed to infants with little side effects (Badger, Ronis, Hakkak, Rowlands, & Korourian, 2002;Motil, 2000;Seppo et al, 2005). Such widespread use suggests that therapeutic-containing soy formulations would not pose any significant risk, supporting the notion that transgenic soybean formulations would not require purification of the protein prior to treatment.…”
mentioning
confidence: 99%